Heritage discourses in Europe : responding to migration, mobility, and cultural identities in the twenty-first century - Colomer, L. (Laia); Catalani, Anna (Collection development, cultural heritage, and digital humanities., 2020)
Debates about migration and heritage largely discuss how newcomers integrate into the host societies, and how they manage (or not) to embrace local and national heritage as part of their new cultural landscape. But relatively little attention has been paid to how the host society is changing culturally because its new citizens have collective memories constructed upon different geographies/events, and emotional attachments to non-European forms of cultural heritages. 0This book explores how new cultural identities in transformation are challenging the notions and the significance of heritage today in Europe. It asks the questions: How far are contemporary Authorized Heritage Discourses in Europe changing due to migration and globalization? Could heritage sites and museums be a meeting point for socio-cultural dialogue between locals and newcomers? Could heritage become a source of creative platforms for other heritage discourses, better "tuned" with today?s European multicultural profile?